Suku Bunga Penjaminan dan Imbal Bagi Hasil (Yield Rates) Deposito Mudharabah: Peran Likuiditas Sebagai Pemoderasi - Cut Dian Fitri; Khairul Amri; Ikhsan Ikhsan (Universitas Batanghari Jambi, 2022)
This study aims to analyze the effect of the deposit insurance interest rate on the yield rates of mudharabah deposits at Islamic commercial banks in Indonesia. Bank liquidity was positioned as a moderating variable. Using monthly time-series data over January 2015 -March 2021, sourced from finance statistical reports published by the Financial Services Authority (OJK) and the Indonesian Deposit Insurance Corporation (LPS). The analytical model applied comprises simple linear regression and moderated regression analysis (MRA) which is then estimated using the Ordinary Least Square (OLS) approach. The study pointed out that the deposit insurance interest rate has a positive and significant effect on the yield rates of mudharabah deposits. Sharia commercial banks responded to the increase in deposit insurance interest rates by increasing the deposit yield rates. Bank liquidity does not significantly affect yield rates, except for time deposits over 12 months, but this variable moderates the effect of the deposit insurance interest rate on yield rates for time deposits of 1 month, 6 months, and > 12 months. The moderating effect is negative, such as reducing the positive impact of deposit insurance interest rate on the yield rates of the three category of time deposits.